Mindfulness in the workplace: an introduction - Imbusch, Niamh (Henry Stewart Talks, 2024)
Definition of mindfulness, Mindfulness-based interventions (MBIs), S-ART Model, Stress, Consequences of stress, Pros and cons, Upstream thinking